Jewishness and postcoloniality in Borges and Derrida: the singular and the specific. Issue 8 (3rd August 2022) - Chapman, Edmund
ABSTRACT: This paper reads two texts, 'The Argentine Writer and Tradition' by Jorge Luis Borges and Monolingualism of the Other by Jacques Derrida, to examine the tension between singularity and specificity in comparative work, particularly in comparisons between Jewishness and postcoloniality. 'Singularity' is understood here as uniqueness, while 'specificity' is the factors that define that uniqueness. Borges' text serves as an example of the potential pitfalls of comparative work that is inconsistent in its recognition of singularity and specificity. Borges affords Jewish writers singularity, but not specificity, and so ends up denying the very elements of Jewish culture his argument appears to valorise, at the expense of his celebration of the postcolonial condition. Borges' comparison therefore undermines its own logic. Derrida, meanwhile, appears to exaggerate one particular colonised Jewish community's exceptionality, but through this apparent focus on the specificity of one group at the expense of others, offers a potential model for how to work comparatively yet still recognise the specificity of multiple groups.